Misrepresentation of thermal stability across different oxidation states of copper compounds by SCAN meta-GGA functionals - Soungmin Bae; Noriyuki Egawa; Hannes Raebiger (Scientific Reports)
Abstract The Strongly Constrained and Appropriately Normed (SCAN) meta-GGA (generalized gradient approximation) density functional and its regularized derivatives (e.g., SCAN and r2SCAN) have been proposed as a post-standard exchange-correlation functional, and are widely believed to replace conventional GGA functionals (e.g. PBE-GGA) owing to greatly improved electronic structures of strongly correlated systems and overall accuracy of total energies. While these improvements have been widely demonstrated for various systems, we report a significant failure of SCAN functionals related to erroneous stability of multivalent states of copper: SCAN and its derivatives (r2SCAN) critically fail to predict the relative stability of copper in oxidation states Cu+ 1(d 10) and Cu+ 2(d 9), excessively stabilizing Cu+ 2 over Cu+ 1, which leads to wrong relative stability of Cu2O and CuO. This spurious bias also results in unphysical oxygen defect structures of YBa2Cu3O7–δ for small δ. While the PBE-GGA functional can be fixed with a simple Hubbard-U correction (PBE + U) to predict both the spectral and thermochemical properties of copper compounds correctly, this is shown to not be the case for SCAN functionals. Our work advocates careful consideration of SCAN meta-GGA functionals when they are applied for cuprate superconductors, catalysis, and defect studies of copper compounds.